2010
DOI: 10.1136/jcp.2010.076562
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the correlation between grading and histology of solitary pulmonary nodules and contrast enhancement and [18F]fluorodeoxyglucose standardised uptake value after evaluation by dynamic multiphase CT and PET/CT

Abstract: AimTo evaluate whether the histology and grading of solitary pulmonary nodules (SPNs) correlated with the results of dynamic multiphase multidetector CT (MDCT) and the [18F]fluorodeoxyglucose standardised uptake value (SUV) in 30 patients.MethodsChest x-rays of 270 patients with incidentally detected SPNs were retrospectively evaluated. Thirty patients with histologically proven SPNs were enrolled. On MDCT and positron emission tomography (PET)/CT images, two experts measured the density of nodules in all perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…24 Similar results have also been reported between standardized uptake value and microvessel density and histological grading. 25 Therefore, CT and positron emission tomography (PET)/CT may play an important role in evaluating the neovascularization of pulmonary nodules. However, a comparative study on the value of routine CT scan with dynamic CT or PET-CT in evaluating the neovascularization of pulmonary nodules is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…24 Similar results have also been reported between standardized uptake value and microvessel density and histological grading. 25 Therefore, CT and positron emission tomography (PET)/CT may play an important role in evaluating the neovascularization of pulmonary nodules. However, a comparative study on the value of routine CT scan with dynamic CT or PET-CT in evaluating the neovascularization of pulmonary nodules is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Interestingly, an increased glucose metabolism measured as SUV might have a prognostic value in terms of tumor progression, recurrence, and hazard of death. 30 – 32 However, Cappabianca et al 33 reported no correlation between SUV and grading of malignant SPN.…”
Section: Discussionmentioning
confidence: 99%
“…As the EES pressure increases, the contrast media passes back into the vessel rapidly. Normally, a higher K ep indicates a higher cell density and vascular permeability of malignant tissue (25). The malignant SPN tissue has a higher microvascular density due to tumor angiogenesis and results in much more permeable capillaries (17,26).…”
Section: Comparison Of 18 F-fdg Pet/ct and Dce-mri Parametersmentioning
confidence: 99%